Students’ Writing Ability on Islamic Narrative Text Topic - Sri Rahmadhani Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The research focused on students’ writing ability on Islamic narrative text topic at XI grade students MA An-Nur Padangsidimpuan. It was done through quantitative research. There were 11 students as samples of the research. The students’ ability was measured by giving them essay test in writing about Islamic topic such prophet story. The data was analyzed by calculating students’ mean score to decide students’ ability category. Based on the result of research, students’ mean score was 75.09. It means that, the students’ ability categorizes into good category.